Echocardiographic assessment of global longitudinal right ventricular function in patients with an acute inferior ST elevation myocardial infarction and proximal right coronary artery occlusion - Hutyra, Martin; Skála, Tomáš; Horák, David; Köcher, Martin; Tüdös, Zbyněk; Zapletalová, Jana; Přeček, Jan; Louis, Albert; Smékal, Aleš; Táborský, Miloš (The international journal of cardiovascular imaging, 2015)
Right ventricular (RV) myocardial infarction (MI) is a frequent concomitant of an acute inferior MI. We set out to determine the diagnostic value of speckle tracking echocardiography in comparison with cardiac magnetic resonance (CMR) for RV stunning and scar prediction. 55 patients (66 ± 11 years) with an acute inferior ST elevation MI who underwent percutaneous coronary intervention (PCI) of an occlusion in the proximal right coronary artery were prospectively enrolled. An echocardiography was done on the day of presentation and on the 5th day thereafter. A CMR was subsequently performed 1 month after the MI. The CMR was used to differentiate between the group with RV scar (n = 26) and without RV scar (n = 29). RV peak systolic longitudinal strain (RV-LS) at presentation determined RV scar (-21.1 ± 5.1% vs. -9.9 ± 4.6%, p < 0.0001). The RV-LS correlated with the scar extent (r = 0.83, p < 0.0001). RV-LS > -15.8% had a sensitivity of 92% and a specificity of 83% in RV scar prediction (AUC 0.93). RV-LS was superior to TAPSE and TDI in determining the presence of RV scar. According to RV-LS values at presentation and on the 5th day, 3 subgroups were defined: G1-normal deformation (RV-LS <-20%), G2-RV stunning (baseline RV-LS >-20%, 5th day RV-LS <-20%) and G3-persistent RV dysfunction (unchanged RV-LS > -20%). In G1, there was neither RV scar nor clinically relevant hypotension. In G2, 58% of patients developed RV scar and 36% had hypotension. In the G3, 83% developed RV scar and 55% had hypotension. The myocardial deformation analysis could provide an early prediction of RV scar. It allowed the patients to be divided into subgroups with normal RV function, stunning and persistent RV dysfunction.
Keywords: Magnetic Resonance Imaging; Inferior Wall Myocardial Infarction; Ventricular Dysfunction, Right; Female; koronární okluze; ženské pohlaví; Predictive Value of Tests; Myocardial Contraction; prediktivní hodnota testů; časové faktory; Time Factors; lidé; Recovery of Function; magnetická rezonanční tomografie; Coronary Occlusion; dopplerovská echokardiografie; funkce pravé komory srdeční; prognóza; Echocardiography, Doppler; ROC křivka; obnova funkce; Humans; infarkt myokardu spodní stěny; Ventricular Function, Right; prospektivní studie; Male; Hypotension; Aged; Prospective Studies; dysfunkce pravé srdeční komory; Prognosis; hypotenze; lidé středního věku; plocha pod křivkou; senioři; mužské pohlaví; kontrakce myokardu; Myocardium; myokard; Middle Aged; ROC Curve; Area Under Curve